Comparative Efficiency Analysis of Conventional and Islamic Commercial Banks in Indonesia, 2020–2024: Evidence from Data Envelopment Analysis (DEA) - Denia Maulani; Kusnadi (Yayasan Sinergi Kawula Muda, 2026)
Indonesia operates a dual banking system in which Conventional Commercial Banks (BUK) and Islamic Commercial Banks (BUS) coexist under OJK supervision, yet an updated post-pandemic empirical reassessment covering the full 2020–2024 window that jointly applies CRS and VRS specifications and complements DEA with a formal non-parametric group comparison remains limited. This study estimates an output-oriented intermediation DEA model under both specifications using four inputs (total assets, operating expenses, third-party funds/DPK, and capital) and four outputs (loans or financing, interest income or profit-sharing, net income, and operating income) for a purposive sample of 11 BUK and 5 BUS (n = 80 bank-year observations). Because the Shapiro–Wilk test rejected normality for both groups under both specifications (p < 0.001), the Mann–Whitney U test was employed. Under CRS, Asymp. Sig. = 0.194 (> 0.05) indicates no significant overall technical-efficiency gap; under VRS, Asymp. Sig. = 0.018 (< 0.05) indicates a statistically significant difference with BUS attaining a higher mean rank (48.46 vs. 36.88), best interpreted as a scale-adjusted pure technical efficiency advantage. Both bank categories recorded mean efficiency scores below 1.00 under both specifications, signalling persistent inefficiency; the significant VRS result combined with the non-significant CRS result indicates that BUS inefficiency is largely scale-driven rather than managerial. Findings should be interpreted with caution given the inherently small BUS sample (n = 5 banks), which constrains statistical power and limits generalizability beyond the study's inclusion criteria.